When the dark ones gain power: Perceived position power strengthens the effect of supervisor Machiavellianism on abusive supervision in work teams. (September 2016) - Wisse, Barbara; Sleebos, Ed
Abstract: Previous work has focused on the potential maladaptive consequences of the Dark Triad personality traits (i.e., Machiavellianism, psychopathy, and narcissism) in organizational contexts. This research builds upon this work, examining the influence of supervisor position power on the relationship between supervisor Dark Triad traits and abusive supervision in teams. Regression analysis on the data of 225 teams revealed that supervisor Machiavellianism is positively related to abusive supervision in work teams, but only when supervisors perceive their position power to be high rather than low. We discuss how power may function as an amplifier, bringing behavioral consequences of predispositions, emotions and beliefs to the forefront. We also focus on the value of differentiating between the three Dark Triad traits in order to more fully understand how they may relate to the abuse of employees. Highlights: Supervisor Machiavellianism relates positively to abusive supervision in the team. Supervisor position power amplifies this effect. Supervisor narcissism and psychopathy are not related to abusive supervision. Organizations should be cautious when granting power to Machiavellian supervisors.